2005
DOI: 10.1002/app.22255
|View full text |Cite
|
Sign up to set email alerts
|

Electrical and mechanical behaviors of carbon nanotube‐filled polymer blends

Abstract: Four carbon nanotube (CNT)-filled polymer blends, i.e., CNT-filled polyethylene terephthalate (PET)/ polyvinylidene fluoride, PET/nylon 6,6, PET/polypropylene, and PET/high-density polyethylene blends, have been injection-molded and characterized in terms of their microstructures, electrical conductivities, and mechanical properties. The distribution of CNTs in the polymer blends has been examined based on their wetting coefficients and minimization of the interfacial energy. The electrical conductivity and me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
55
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(57 citation statements)
references
References 31 publications
1
55
0
1
Order By: Relevance
“…[1,[10][11][12][13][14][15][16][17][18][19][20] Some of the authors compared the predication of the wetting coefficient or equivalent equations that describe the localization of conductive fillers in an immiscible two phase blend to their experimental observations. [2,5,9,10,19,21] Preferential localization of a filler in one of the phases is commonly explained by the differences in interfacial energies of the filler and the respective polymers, which originates from the differing polarities and surface energies. In general, the authors used polymers that show pronounced differences in surface energies and polarities and, therefore, received distinct predications of the wetting coefficients.…”
Section: Introductionmentioning
confidence: 98%
“…[1,[10][11][12][13][14][15][16][17][18][19][20] Some of the authors compared the predication of the wetting coefficient or equivalent equations that describe the localization of conductive fillers in an immiscible two phase blend to their experimental observations. [2,5,9,10,19,21] Preferential localization of a filler in one of the phases is commonly explained by the differences in interfacial energies of the filler and the respective polymers, which originates from the differing polarities and surface energies. In general, the authors used polymers that show pronounced differences in surface energies and polarities and, therefore, received distinct predications of the wetting coefficients.…”
Section: Introductionmentioning
confidence: 98%
“…[19][20][21][22][23][24] These studies suggested that the material with the lower surface energy is likely to be segregated into the air/fi lm interface while the material with higher surface energy is segregated to the fi lm/electrode interface, indicating that the vertical phase separation is strongly dependent on the surface energy of each material. For ternary blend fi lms, in which a third material is added to binary blends, the location of the third component has been studied for various materials such as conductive carbon black particles, [ 25 ] carbon nanotubes, [26][27][28] CaCO 3 nanoparticles, [ 29 ] and polymers. [ 30 ] These studies indicated that the location of the third component can be predicted in terms of the surface energy of each component in the ternary blends, which is in good agreement with the observation of transmission electron microscopy (TEM) images.…”
Section: Introductionmentioning
confidence: 99%
“…Plasticizers have been used in carbon black / elastomer composites to achieve improved mechanical properties, including hardness, elastic modulus and elongation at break, as compared to the elastomer [13]. Wu et al have reported a two-phase conductive composite system in which most of the SWCNTs are located in the continuous polymer matrix, while a dispersed polymer phase modifies the mechanical and rheological properties of the composites [14].…”
Section: Introductionmentioning
confidence: 99%